2019
DOI: 10.1177/1557988319851954
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Selected Elements and Antioxidative Potential in a Group of Males Working in the Metal Industry: Elements And Antioxidative Potential In Men

Abstract: The purpose of this study was to show that some elements have a proven antioxidative effect and are essential for the proper development and functioning of the human body. The study also assessed the concentration of selected elements and total antioxidant status (TAS) in a group of male inhabitants of Białystok, Poland, who are professionally active in the metal industry. The study group comprised 163 men aged 55–64 years. The concentration of the analyzed elements was determined using flame (Zn and Cu) and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…The work environment is a significant source of lead exposure for many, and leads to numerous health issues and employee absenteeism [38]. Many workers, such as miners and steel workers, welders, plumbers and fitters, car mechanics, glass producers, construction workers, battery manufacturers and recyclers, shooting range employees and plastics manufacturers, are exposed to risk of contact with lead [2].…”
Section: In the Environmentmentioning
confidence: 99%
“…The work environment is a significant source of lead exposure for many, and leads to numerous health issues and employee absenteeism [38]. Many workers, such as miners and steel workers, welders, plumbers and fitters, car mechanics, glass producers, construction workers, battery manufacturers and recyclers, shooting range employees and plastics manufacturers, are exposed to risk of contact with lead [2].…”
Section: In the Environmentmentioning
confidence: 99%
“…Another study found a higher average Pb blood lead concentration (33 ± 9.6 µg/L) in a group of male employees mills in southern Poland (Śląskie Voivodeship). Other workers who were professionally exposed to heavy metals in mills in Legnica and Głogów had a 10 times higher Pb concentrations [25] than a group of men working in the metal industry in Podlasie Voivodeship [31]. The results indicate that men who are occupationally exposed to heavy metals should be carefully monitored to preserve their health [31].…”
Section: Lead Exposure In Polandmentioning
confidence: 99%
“…The work environment is a significant source of lead exposure for many, which in consequence leads to numerous disorders and absenteeism of the employees of the metallurgical industry [31]. Many professional groups, such as miners and steel workers, welders, plumbers and fitters, car mechanics, glass producers, construction workers, battery manufacturers and recyclers, shooting ranges and plastics manufacturers, are exposed to risk of contact with lead [2].…”
Section: Lead Exposure In Polandmentioning
confidence: 99%
See 1 more Smart Citation
“…The adverse health impacts include IQ deficiency, attention and behavioral problems, and poor academic achievement [ 4 , 29 , 30 ] and subsequent long-term impacts, such as reduction in chronic neurological damage leading to potential unemployment and crime [ 31 , 32 , 33 ]. Studies have also shown that lead, along with other heavy metals found in metallurgical industries, can lead to such adverse health effects as cardiovascular diseases in middle-aged men [ 34 ]. Other studies have also show links between elevated lead concentrations in the blood and placenta of pregnant women and the occurrence of miscarriage [ 35 ].…”
Section: Introductionmentioning
confidence: 99%